The Pompeian Connection: A Social Network Approach to Elites and Sub-Elites in the Bay of Naples - Broekaert, Wim (Journal of historical network research, 2020)
This paper focuses on the composition and interaction of Pompeian elite and sub-elite networks and the way in which these relationships shaped and transformed local politics. SNA can contribute to the ongoing debate on the composition and alleged stability or turnover within the Pompeian aristocracy. This dispute has a long tradition and the picture of the Pompeian society emerging oscillates between a democratic community with high levels of social and political mobility and a more traditional Roman city with well-established families dominating the political scene and newcomers rising and disappearing in the margin. I shall analyze and compare the different networks members of elites and sub-elites were circulating in and how they attempted to use, share, extend and manipulate networks to achieve their goals. The key to power thus lies in moving oneself in the most interesting position in the network, either through mobilizing inherited connections, power and wealth or carving out a new location by means of personal assets. The following sections will show how Pompeian elites, established families and newcomers alike, tried to find the most valuable position in the local network and consequently captured the inherent benefits of connectivity.